(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The work will show the fates and reasons that reveal the essence of the empire’s arrival in the region. The changes that occurred in Central Asia with the advent of Russia are history, culture, traditions, mentality. many other directions that have changed since Russia’s arrival in the region. The article contains facts about the changes that occurred in the industrial sector in Central Asia with the arrival of Russia in the region, the essence of the work is to tell about these changes and their significance in history.